Research trends in rabies vaccine in the last three decades: a bibliometric analysis of global perspective. Issue 9 (2nd September 2021) - Ahmad, Tauseef; Haroon; Khan, Muhammad; Murad, Manal Abdulaziz; Baig, Mukhtiar; Murtaza, Bibi Nazia; Khan, Muhammad Mumtaz; Harapan, Harapan; Hui, Jin
ABSTRACT: Introduction: Rabies is an infectious zoonotic viral disease which mainly occurs in Africa and Asia. Dogs are predominantly responsible for rabies transmission contributing up to 99% of all human rabies cases. Rabies is a vaccine preventable disease in both animals and humans. Objective: This study aimed to quantify and characterize the scientific literature and identify the top most cited studies in rabies vaccine research (RVR) from 1991 to 2020. Methods: The data used in this study were downloaded from Web of Science Core Collection (WoSCC), Science Citation Index-Expanded (SCI-E) database. Network visualization analysis was performed using VOSviewer software. Results: A total of 1, 042 papers (article: n = 986, 94.6%, review: n = 56, 5.4%) were included in this study. These have been cited 17, 390 times with an average citation per paper was 16.69 times. The most frequent publication year was 2019 (n = 75, 7.2%). More than 55% studies were published from the United State of America (USA) (n = 380, 36.5%), France (n = 128, 12.3%), and China (n = 97, 9.3%). The most studied Web of Science (WoS) category was immunology (n = 344, 33%). The most prolific author in RVR was Rupprecht CE (n = 55, 5.3%). ' Vaccine' was the leading journal (n = 218, 20.9%). Rabies was the most widely used keyword. Conclusion: Abundant literature has been published on RVR in developed countries. This study might provide a reference to understand the current and future research trends in RVR. In developing countries research collaboration and co-operation among institutes and researchers needs to be strengthened with developed countries.